Snoezelen or Controlled Multisensory Stimulation. Treatment Aspects from Israel - Joav Merrick; Carmit Cahana; Meir Lotan; Isack Kandel; Eli Carmeli (The Scientific World Journal)
In Israel today, with a total population of over 6 million persons, the Division for Mental Retardation (DMR) provides services to 23,000 persons with intellectual disability (ID). Of the 23,000, residential services are provided to more than 6,000 in close to 60 residential centers, another 2,000 are provided residential care in hostels or group homes in the community in about 50 locations, while the rest are served with day-care kindergarten, day-treatment centers, sheltered workshops, or integrated care in the community. The first Snoezelen room (controlled multisensory stimulation) in the DMR was established at the Bnei Zion residential care center in 1995. The Snoezelen method is now used in Israel in more than 30 residential care centers and 3 community settings. Since the year 2000, a physiotherapist has been employed in order to supervise the treatment and development of the method nationally. Professional staff meetings take place every 4 months. A certification course has been established on a national basis for individuals from different professions (occupational therapists, physiotherapists, teachers, music therapists, nurses, speech therapists, or caregivers). Snoezelen has proved to be an important instrument and a powerful therapeutic tool among the various treatment modules employed in Israel for persons with ID. This paper presents the concept illustrated with two case stories.